Research circles: A method for the development of knowledge and the creation of change in practice - Sara Högdin; Cecilia Kjellman (Escola Superior de Educação de Paula Frassinetti, 2014)
This article contains a presentation of experiences gained of research circles as a participant-based method for the development of knowledge and the creation of change in practice. The starting point is two international projects whose aim is to develop knowledge about the professional work being done with young people who exhibit violent behavior. In the Swedish sub-studies, research circles are used as a method for developing such knowledge as well as for creating change in practice. The research circle as a method has its theoretical starting point in action research and participant-oriented research. The results of the study illustrate how research circles can contribute to the creation of a knowledge process through the dialogue in the group and the facilitation of reflection over different work approaches in one's own work, even if it is a method that does not suit everyone. The results also show that the research circle can lead to a change process in the actual work by enhancing transprofessional collaboration and leading to an increase in the participants' awareness and evaluation of their work with violent children and young people